The Issue Of Christian Anthropology - Kuc, Leszek (Studia Theologica Varsaviensia, 2020)
2e text of Gaudium et spes has not yet become the basis for a systematic analysis from the point of view of Christian anthropology+>. We shall not conduct a systematic analysis at the end of this article. We will only mention a few issues that are particularly important in our opinion. 2e first issue is the very arrangement of the first chapter of the Constitutions. It speaks firstly of the dignity of the individual, then of the human community, and only then does it move on to the discussion of human activity in the world and the tasks of the Church in the modern world. 2e anthropological concept of the text can be seen from the very layout of the chapters of the first part. 2e idea is that the concept of the presence of the Church in the contemporary world, that is, the concept of the Church as a sign, that is, a modern concept of pastoral ministry with the whole Church as a subject, depends on the right attitude and resolution of the question of who I am and who I – man – become. 2is is the basic premise of an anthropological structure, expressed in questions about the dignity of the person and the human community.